2013
DOI: 10.1515/iral-2013-0013
|View full text |Cite
|
Sign up to set email alerts
|

Prototypical influence in second language acquisition: What now for the Aspect Hypothesis

Abstract: This paper presents empirical evidence on the development of aspect byEnglish-and German-speaking university learners of French L2 collected from a spoken narrative task and a sentence interpretation task. Contrary to the Aspect Hypothesis's predictions, this study's results suggest that increased use of prototypical pairings goes in hand with increased L2 proficiency. Following a small but growing number of studies, this study questions the route of L2 development proposed by the Aspect Hypothesis.Prototypica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
51
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 25 publications
4
51
0
1
Order By: Relevance
“…Future research using picture-based narratives should investigate how different prompt types (adverb, verbal) and their frequency affect L2 production. Third, although this paper is part of a larger study on the L2 development of aspect morphology in French L2 (see McManus, 2011aMcManus, , 2013, the present analysis is based on data collected from one instrument.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Future research using picture-based narratives should investigate how different prompt types (adverb, verbal) and their frequency affect L2 production. Third, although this paper is part of a larger study on the L2 development of aspect morphology in French L2 (see McManus, 2011aMcManus, , 2013, the present analysis is based on data collected from one instrument.…”
Section: Limitationsmentioning
confidence: 99%
“…The AH predicts learners' early use of aspect morphology will be heavily influenced by lexical aspect: perfective morphology (e.g., passé composé) will be initially used with telic predicates, and imperfective morphology (e.g., imparfait), with atelic predicates. It is claimed that, as L2 proficiency increases, learners begin to use aspect morphology, irrespective of a predicate's lexical class (although see Domínguez, Tracy-Ventura, Arche, Mitchell, & Myles, 2013;McManus, 2013). Furthermore, Andersen's (1984) one-to-one principle has been shown to be insightful in predicting initial form-meaning mappings.…”
mentioning
confidence: 99%
“…SLA research shows patterns of learning associated with IMP's different viewpoint aspect meanings that can be attributed to different cue validities in L1 and L2 (Ayoun, , ; Howard, ; Kihlstedt, ; McManus, , ). Given that IMP is used to express both past ongoingness and past habituality, research indicates (a) that these viewpoint aspect meanings are not acquired together, and (b) that the acquisition order of these meanings appears to be influenced by L1 background: Ongoingness is acquired before habituality for English‐speaking learners (Howard, ), but habituality is acquired before ongoingness for Swedish‐speaking learners (Kihlstedt, ).…”
Section: Introductionmentioning
confidence: 99%
“…A MAJOR FOCUS OF SECOND LANGUAGE acquisition (SLA) research to date has sought to understand the competition and relationships between a learner's different languages (Calabria et al., ). This research has repeatedly shown that the use of a single language activates a speaker's other known languages (Marian & Spivey, ; Wu & Thierry, ), that prior first language (L1) knowledge and experience can influence second language (L2) use (e.g., selective attention to linguistic cues; Ellis & Sagarra, ; MacWhinney, ), and that L1–L2 differences can influence the route and rate of L2 morphosyntactic development and processing (Avery & Marsden, 2019; Isabelli, ; McManus, , ; Murakami, ; Roberts & Liszka, ). However, despite major advances in what we know about the cognitive effects and mechanisms of learning a second language, little research has systematically examined the next step in this program: How can this understanding about the competition and relationships among a learner's different languages be used to facilitate L2 learning and teaching?…”
mentioning
confidence: 99%
See 1 more Smart Citation